3D Geo Information System - where are we? - Abdul Rahman, Alias; Zlatanova, Sisi; Coors, Volker; Gold, Chris (2007)
GIS evolves from a simple to advanced information system and yet we have seen many situations where these information systems were unable to provide satisfactory solutions and answers to users. More and more users are now looking for advanced and reliable systems. The problem becomes more apparent when it comes to manipulating and handling 3D spatial objects either in standalone, wired or mobile computing environment system. There are a number of challenges and issues still need to be addressed for a more decent 3D spatial information system as we used to have in 2D domain. This paper reviews recent research works toward realizing 3D geoinformation system. Discussions on spatial data modeling including spatial operators, databasing for 3D spatial objects, and utility objects form major part of the paper. The paper also describes research works on 3D Web services and the related applications such as indoor and outdoor navigation as part of solution for city modelling and way finding within building environment. Furthermore, current status of the research and development works on 3D geoinformation will be highlighted and finally, a discussion on future trend on the development of 3D geoinformation system and services.